The Impact of Social Media JN Privacy and Their Role in Decision Making (Global Journals of Research in Engineering, 2022)
Social media has been rumored in recent years, with social media not only referring to the popular but also the less popular, as well as targeted social media, including the collection. and analysis of information which information is then used for other purposes. Social media offers users plenty of features and smart features using artificial intelligence while making the most of the internet. Through the use of social media, it is possible to manage and view information from smart devices, also known as IoT. This implies on the one hand freedom of interfaces and freedom of operations and on the other hand implies an increased risk of privacy violations combined with the possibility of illegal access and control of smart devices. Various countries around the world have created cyber armies that use a variety of techniques - including social media - to monitor, suspend, and internally influence the functioning of states and directly influence decision-making, and generally intervene in the operation in another country, a typical example is the deepfake of politicians using social media to influence public opinion. As a result of the large amount of personal data that users themselves enter in various ways on social media is the source of information that can be exploited and used for other purposes including marketing. There is no clear indication of who is actually the owner of this information, in many cases there is a difference from the terms of use of the services and the national legislation of the country in which a social media company is based or have the facilities there. which are entered into social media databases are never deleted, the deletion of personal information by the user should not be considered, for example the deletion of photos given, should be considered an invisible and not deleted permanently. This contributes to the exchange of information with government agencies and the creation of electronic profiles of people and their habits. Social media does not have the same impact on the public, the reasons are many, such as for example there are people who know what happens to personal data, so they are skeptical about the content they choose to share on social media, others users avoid the use of social media, other users due to social beliefs avoid the use of social media. On the other hand, social media offers tempting applications and functionality to the users in order to bend as much as they can the most skeptical users using applications and services of artificial intelligence in order to bend any problems that arise. Users seem to be indifferent to what is really going on from the use of their personal data. In the boom of communication and the intelligent possibilities offered by information technology, the sectors, privacy, security, and digital freedom of people are sacrificed as social media does not offer access to their users regarding the collected personal data, nor is it given to them users to set the collection of personal data they want. Due to socialization and globalization, social media has become necessary for the socialization of people, so it can be considered that there is a human consensus for the violation of his privacy which is socially legitimate. In the future there is expected to be a new condition for the defined privacy as the facts of the time change and the definition in new orders of things must be adjusted.
Keywords: social media; privacy; surveillance; violation; decision making; e-profile